1996
DOI: 10.1111/j.1432-1033.1996.0778p.x
|View full text |Cite
|
Sign up to set email alerts
|

The Anticoagulant Effect of the Human Secretory Phospholipase A2 on Blood Plasma and on a Cell‐Free System is Due to a Phospholipid‐Independent Mechanism of Action Involving the Inhibition of Factor Va

Abstract: Blood platelets play a central role in haemostasis by leading to plug formation and by increasing the efficiency of blood coagulation. We have previously shown that blood platelets contain a group I1 secretory phospholipase A, (sPLA, grII) which is released into the extracellular medium upon activation but is unable to stimulate blood platelets. We presently reported an investigation of the putative involvement of the human sPLA, grII (hsPLA, grII) in the coagulation process, both in the absence and in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
41
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 49 publications
0
41
0
1
Order By: Relevance
“…Actually, this procoagulant nature was not anticipated, because previous studies showed that sPLA 2 , which is present in high concentrations in synovial fluid, inhibits coagulation (23,24,37,38). In line with such an effect of sPLA 2 was the lower exposure of PS by synovial microparticles, as reflected by the reduced binding of annexin V, most likely due to the breakdown of PS to lyso-PS.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, this procoagulant nature was not anticipated, because previous studies showed that sPLA 2 , which is present in high concentrations in synovial fluid, inhibits coagulation (23,24,37,38). In line with such an effect of sPLA 2 was the lower exposure of PS by synovial microparticles, as reflected by the reduced binding of annexin V, most likely due to the breakdown of PS to lyso-PS.…”
Section: Discussionmentioning
confidence: 99%
“…To date, nine genes coding for structurally related and enzymatically active sPLA 2 s have been identified in mammals (groups IB, IIA, IIC, IID, IIE, IIF, III, V, and X) (6 -10). Understanding the physiological functions of this diverse set of sPLA 2 s is now a complex and challenging area of research in the eicosanoid field, and the possibility that some of these enzymes are involved in processes unrelated to eicosanoid generation should be considered (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…Group IIA sPLA 2 (sPLA 2 -IIA), known as inflammatory PLA 2 , is expressed in a variety of tissues and hematopoietic cells, and its expression is markedly induced following challenge with proinflammatory stimuli (1,(23)(24)(25)(26). This sPLA 2 is thought to play a role in inflammation (1), host defense against bacteria (13)(14)(15), tumor suppression (16), exocytosis (17,18), blood coagulation (19), and atherosclerosis (20,21). Group IIC sPLA 2 (sPLA 2 -IIC) is expressed in rodent testes, but only a pseudogene for this enzyme has been found in the human genome (5,27).…”
mentioning
confidence: 99%
“…The prothrombinase complex, composed of FVa, FXa, phospholipids (PL), and Ca 2ϩ , plays a central role in the coagulation cascade (17,21). hsPLA 2 exerts a moderate anticoagulant effect on plasma (22) and inhibits prothrombinase activity (23,24). The anticoagulant effect of hsPLA 2 is phospholipid-independent and not observed when FV-deficient plasma is used for coagulation assays (24).…”
mentioning
confidence: 99%